CRITICAL DISCUSSION ANALYSIS ABOUT THE REPRESENTATION OF ANTI-BULLYING CULTURE IN "GAJAH" SONGS OF TULUS WITH TEUN A. VAN DIJK APPROACH - Nychken Gilang Bedy S; Muhammad Azhari; Wikanengsih Wikanengsih (JLER (Journal of Language Education Research), 2018)
Bullying case is rife in Indonesia, it is a severe blow to the pattern of Indonesian education. Bullying does not only hurt someone physically but further psychologically. This is the basis for the author to critically analyze the representation of anti-abuse culture found in the song lyrics of "Gajah" song of Tulus using the Teun A. Van Dijk approach as his scalpel. This was done as an effort to participate in the anti-bullying campaign. The song "Gajah" from Tulus was chosen because Tulus was a musician whose songs were heard by various groups. The method used is descriptive which is combined with Teun A. Van Dijk's approach as the research scalpel. The song "Gajah" is considered to have voiced a lot of anti-bullying, starting from someone who is always bullied to being able to rise from bullying. This research is expected to be used as reference material as well as anti-bullying media because the song lyrics of "Gajah" from Tulus are a mirror of the anti-bullying culture that seeks to prevent bully behavior that is prevalent in schools and communities.